Individual, social, and environmental factors for infection risk among home healthcare patients: A multi‐method study. (19th February 2021) - Russell, David; Dowding, Dawn; Trifilio, Marygrace; McDonald, Margaret V.; Song, Jiyoun; Adams, Victoria; Ojo, Marietta I.; Perry, Eun K.; Shang, Jingjing
Abstract: There has been limited research into the individual, social, and environmental factors for infection risk among patients in the home healthcare (HHC) setting, where the infection is a leading cause of hospitalisation. The aims of this study were to (1) explore nurse perceptions of individual, social, and environmental factors for infection risk among HHC patients; and (2) identify the frequency of environmental barriers to infection prevention and control in HHC. Data were collected in 2017–2018 and included qualitative interviews with HHC nurses ( n = 50) and structured observations of nurse visits to patients' homes ( n = 400). Thematic analyses of interviews with nurses suggested they perceived infection risk among patients as being influenced by knowledge of and attitudes towards infection prevention and engagement in hygiene practices, receipt of support from informal caregivers and nurse interventions aimed at cultivating infection control knowledge and practices, and the home environment. Statistical analyses of observation checklists revealed nurses encountered an average of 1.7 environmental barriers upon each home visit. Frequent environmental barriers observed during visits to HHC patients included clutter (39.5%), poor lighting (38.8%), dirtiness (28.5%), and pets (17.2%). Additional research is needed to clarify inter‐relationships among these factors and identify strategies for addressing each as part of a comprehensive infection control program in HHC.